2009
DOI: 10.1088/0031-8949/80/05/055602
|View full text |Cite
|
Sign up to set email alerts
|

XAS study of the orientation of oriented carbon nanotube films

Abstract: We report a quantitative x-ray absorption spectroscopy (XAS) study of the orientation of carbon nanotubes (CNTs) grown on plain SiO2(thickness 8 nm)/Si(100) substrates by a catalytically enhanced dc hot filament chemical vapour deposition (CVD) process. The alignment and orientation of CNT films are generally provided in the literature by scanning electron microscope (SEM) and transmission electron microscope (TEM) images qualitatively. A very few other techniques have been used to more deeply study the alignm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…This ratio calculated in Tables 2 and 3 for some CNTs samples is indicative of the orientation tendency of the graphite orbitals [22] and as consequence, the graphene layer's.…”
Section: ( )mentioning
confidence: 89%
See 3 more Smart Citations
“…This ratio calculated in Tables 2 and 3 for some CNTs samples is indicative of the orientation tendency of the graphite orbitals [22] and as consequence, the graphene layer's.…”
Section: ( )mentioning
confidence: 89%
“…The curvature of the graphite sheet is also among those factors that were considered to explain the change of the electronic states in CNSs [36]. The carbon K-edge x-ray absorption spectroscopy [21,37,38] and TEM [21,22] revealed that the features of electronic states of the carbon atoms in the carbon nanostructures are very similar to those of graphite. Thus, the CNSs XANES spectra are very similar to those of graphite and almost identical with that of HOPG (High Oriented Pirolytic Graphite) measured at the magic angle (54.7˚), where no polarization dependence of π-type states occurs.…”
Section: Xanes Spectra Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…49,50 The latter, in particular, revealed to be a powerful tool for investigating nanostructured materials and inner interfaces. 6,51 However, state-of-the-art computational investigations are limited to the crystalline phases of SiC nanowires, [52][53][54][55][56] while the SiC/SiO x interface is modeled only in the case of geometries as slabs or nanodots. 57,58 Furthermore, these models are not enough accurate and realistic for shedding light on the many electronic and structural information enclosed in XANES spectra, and to explain the absorption peak lineshape of several transitions arising from these structures.…”
Section: Introductionmentioning
confidence: 99%